Pengaruh Rasio Keuangan Terhadap Harga Saham Pada Perusahaan PT. Indofood Sukses Makmur Yang Terdaftar Di Bursa Efek Indonesia - Normalina Purba; Nurlinda Nurlinda (CIVITAS: Jurnal Studi Manajemen, 2022)
this study aims to determine whether there is an effect of current ratio, net profit margin, earning per share on stock prices at PT. Indofood Sukses Makmur which was listed on the Indonesia Stock Exchange for the period 2011-2019. Types and sources of data in this study are secondary data in the form of financial statements of PT. Indofood Sukses Makmur which was listed on the Indonesia Stock Exchange in 2011-2019. The data analysis method used in this research is descriptive quantitative method and multiple linear regression analysis model, hypothesis testing using the coefficient of determination (R2), simultaneous test (F test), and partial test (t test) with data processing using SPSS Statistic program 22. The results of this study indicate that the determination coefficient test (R2) yields 0.134 or 13.4% results indicating that the current ratio, net profit margin, earning per share variables can explain the variables that occur in the stock price of PT. Indofood Sukses Makmur, while the remaining 0.866 or 86.6% is explained by other variables which were not researched. The results of the study partially show that current ratio, net profit margin, earning per share have no and insignificant effect on stock prices and simultaneously current ratio, net profit margin, earning per share have no and insignificant effect on stock prices.